Politika - Clancy, Tom, 1947-2013; Clancy, Tom, 1947-2013.; Greenberg, Martin Harry (New York : Berkley Books, 1997)
In the turmoil following the sudden death of the Russian president, American businessman Roger Gordian finds his multinational corporation and its employees in jeopardy, and he sets out to find the terrorists responsible for the assassination.
Based on the Red Storm Entertainment computer game.
Accelerated Reader AR
Keywords: Coups d'ťat -- Fiction; Russia (Federation) -- Fiction; Suspense fiction